The Effect of Product Display and Digital Payment on Impulse Buying - Fiana, Irma Ari; Putri, Kartika Anggraeni Sudiono (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Sales in the retail business continue to increase. In the April 2022 Real Sales Index (IPR), there was an increase in monthly retail sales of 6.8%. Therefore, competition in retail is getting tougher with many emerging competitors. So, a strategy is needed in running the retail business, one of which is a strategy in the product structuring system and also the payment system. This raises interest in analyzing the effect of product displays and digital payments on impulse purchases. This study aims to examine the effect of product displays and digital payments both partially and simultaneously on impulse buying. This study uses quantitative research with the sampling technique used is purposive sampling. The population in this study were consumers who had visited, shopped, and used digital payments at Metro Swalayan Malang with a total sample of 165 obtained through a questionnaire. This study uses SPSS tools with multiple linear regression analysis techniques. The results of the study found that product displays had a significant effect on impulse buying, digital payments did not have a significant effect on impulse buying, and simultaneously product displays and digital payments had a significant effect on impulse buying at Metro Swalayan Malang.